The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ehf2.13641
|View full text |Cite
|
Sign up to set email alerts
|

Body composition analysis in patients with acute heart failure: the Scale Heart Failure trial

Abstract: Aims In this study, we aimed to investigate whether body composition analysis (BCA) derived from bioelectrical impedance vector analysis (BIVA) could be used to monitor the hydration status of patients with acute heart failure (AHF) during intensified diuretic therapy. Methods and results This observational, single‐centre study involved a novel, validated eight‐electrode segmental body composition analyser to perform BCA derived from BIVA with an alternating current of 100 μA at frequencies of 5, 7.5, 50, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…Such dynamic change might reflect that related to the congestion status of HF patients during their clinical in-hospital and out-of-hospital course. Similar results were from De Ieso et al [ 43 ] in patients with ADHF: improvement in PhA was observed during the hospital stay after intensified diuretic therapy.…”
Section: Clinical and Diagnostic Value In Congestion Statussupporting
confidence: 89%
See 2 more Smart Citations
“…Such dynamic change might reflect that related to the congestion status of HF patients during their clinical in-hospital and out-of-hospital course. Similar results were from De Ieso et al [ 43 ] in patients with ADHF: improvement in PhA was observed during the hospital stay after intensified diuretic therapy.…”
Section: Clinical and Diagnostic Value In Congestion Statussupporting
confidence: 89%
“…PhA remained stable at 3-month f.u. 0.7° De Ieso et al 2021 [ 43 ] 142 ADHF Observational Multi-frequency medical whole-body composition analyser (Seca® mBCA 515, Hamburg, Germany) N/A Mean phase angle increased from 3.61 ± 0.82° to 3.83 ± 0.74° from admission to discharge 0.22° Gastelurrutia et al 2011[ 44 ] 54 Stable and unstable HF Observational Imp DF50 (ImpediMed, Queensland, Australia). 50 kHz frequency and 800 microA current N/A Male: PhA: Stable HF 4.5 ± 0.8° vs. unstable HF 3.8 ± 0.7°, p = 0.02 Female: PhA: Stable HF 3.9 ± 0.8° vs. unstable HF 3.9 ± 0.9°, p = 0.96 Male 0.7° Female 0° Massari et al 2016 [ 6 ] 900 487 ADHF and 413 CHF Retrospective CardioEFG, Akern RJL Systems, Florence, Italy Tetrapolar impedance plethysmograph, 50 kHz alternating sinusoidal current N/A Phase Angle ADHF 4.7 ± 1.2° vs. CHF 5.5 ± 1.3° ADHF Phase Angle With peripheral edema: 4.2 ± 1.0° vs. without peripheral edema: 5.1 ± 1.2, p < 0.01 CHF Phase Angle With peripheral edema: 4.5 ± 1.0° vs. without peripheral edema: 5.6 ± 1.2, p < 0.01 ADHF vs. CHF 0.8° ADHF 0.9° CHF 1.1° Castillo Martínez et al 2007 [ 45 ] 243 140 (101 in NYHA I–II and 39 in III–IV) with HFrEF 103 (67 in NYHA I–II and 36 in II–IV) with HFpEF.…”
Section: Bioelectrical Phase Angle: Definition and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a non-invasive method that allows the analysis of the body composition in a few seconds thanks to the detection of the impedance, or the “resistance” opposed by the body to the passage of an alternating electric current of very low intensity (400 µÅ) and high frequency (50 kHz). It is a safe, fast and reproducible method that can be easily integrated into clinical practice to detect patients with congestion (even subclinical) and monitor disease progression and decongestion with diuretic therapy [ 41 ].…”
Section: Malnutrition and Evaluation Of The Nutritional Statusmentioning
confidence: 99%
“…In patients with acute HF, BIA reliably reflects changes in hydration status, correlates with echocardiographic parameters, natriuretic peptide levels, and predicts hospital length of stay. However, BIA-guided decongestive therapy has not shown to be superior compared to standard care with respect to outcome [69][70][71][72]. In critically ill patients, the accuracy of BIA as a measure of hydration status remains unclear at this time [73].…”
Section: Bioimpedance Analysismentioning
confidence: 99%